2022
DOI: 10.3390/ijerph19074263
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory Study of Palliative Care Utilization and Medical Expense for Inpatients at the End-of-Life

Abstract: Background: Previous research mostly analyzed the utilization of palliative care for patients with cancer, and data regarding non-cancer inpatients are limited. Objectives: This research aimed to investigate the current situation regarding palliative care and the important factors that influence its utilization by inpatients (including inpatients with and without cancer) at the end of their lives. We also explored the feasibility of establishing a prediction model of palliative care utilization for inpatients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…PC can improve the quality of patient outcomes [24,35]. Furthermore, several studies have shown that PC reduced the average medical expense of patients with cancer and multiple comorbidities [28,36,37]. Our research shows that the average medical expense is lower in patients with emergency treatment than in those without any emergency treatment at the end of life.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…PC can improve the quality of patient outcomes [24,35]. Furthermore, several studies have shown that PC reduced the average medical expense of patients with cancer and multiple comorbidities [28,36,37]. Our research shows that the average medical expense is lower in patients with emergency treatment than in those without any emergency treatment at the end of life.…”
Section: Discussionmentioning
confidence: 53%
“…The main purposes of PC include satisfying the needs of patients and their family members to ease their pain, improving the patients' dignity at the end of life, and reducing unnecessary treatments [28]. In PC consultations, the patient, family members, and medical team often discuss hospice care plans suitable for the patient.…”
Section: Of 12mentioning
confidence: 99%
“…A systematic review reported that hospital-based specialist palliative care (HSPC), which includes inpatient hospices/PCUs and palliative care teams, reduced patient symptom burden, improved health-related quality of life, other person-centered outcomes, and satisfaction of patients with advanced illness (8). In spite of these clear advantages, inpatient hospices/PCUs have not committed to providing palliative care to non-cancer patients in Taiwan (9). This trend is similar in Japan where specialist palliative care has mainly been developed for advanced cancer patients in the last two decades (10).…”
Section: Introductionmentioning
confidence: 99%
“…The utilization of palliative and hospice care in Taiwan remains relatively low despite the enactment of the Natural Death Act and Hospice Palliative Care Act 7-9 . Health care providers and family caregivers have encountered truth-telling, traditional social norms related to filial piety and hospice referral as common ethical dilemmas 10,11 .…”
mentioning
confidence: 99%
“…6 The utilization of palliative and hospice care in Taiwan remains relatively low despite the enactment of the Natural Death Act and Hospice Palliative Care Act. [7][8][9] Health care providers and family caregivers have encountered truthtelling, traditional social norms related to filial piety and hospice referral as common ethical dilemmas. 10,11 Because of a lack of training in communication and truth-telling skills, health care providers in Taiwan have difficulty in initiating end-of-life care discussions with patients 12 and prefer to discuss sensitive topics with caregivers of patients.…”
mentioning
confidence: 99%